Modern Antisemitism, Nationalism, and the Estate of Clergy in Nineteenth-Century Finland - Ahonen, Paavo (A journal of church and state, 2025)
Finland was an autonomous part of Russia from 1809 to 1917. Jews had no civil rights in Russia, and in addition, Finland was permitted to retain old Swedish laws, which stated that Jews had no right to reside in Finland. In the late 1850s, Tsar Alexander II allowed Jewish soldiers who had served in the Imperial Russian Army to settle in their station cities. The Jewish minority in Finland originally consisted of these soldiers and their families. The debate over Jewish civil rights began in the Diet of Finland in the 1870s. This article describes the debate on the Jewish question in the Estate of Clergy from 1872 to 1897. It examines how Jews were portrayed and how the rise of modern political antisemitism affected the rhetoric, argumentation, and possibly the outcome of the discussion. Around the same time, so-called modern political antisemitism started to spread across Europe. Antisemitism has its roots deep in Christianity, and studying the Clergy opens up a possibility to examine the intersection between religious and secular modern antisemitism. Additionally, this article explores how Jews were perceived from the perspective of nationalism at a time when Finland was undergoing a nation-building process.